Crime in progress : inside the Steele dossier and the Fusion GPS investigation of Donald Trump - Simpson, Glenn R; Fritsch, Peter (Journalist) (Random House, 2019)
"The never-before-told inside story of the high-stakes, four-year-long investigation into Donald Trump's Russia ties--culminating in the Steele dossier, and sparking the Mueller report--from the founders of political opposition research company Fusion GPS" -- Amazon.com.